The therapeutic futility paradox: insights from oncological drug litigation in Ecuador - Mena Ayala, María Belén; Maldonado, Xavier (Frontiers in Medicine, 2025)
BackgroundIn oncology, patients with advanced cancer are often subjected to treatments with limited therapeutic value. This phenomenon is amplified through drug litigation, where interpretations of the right to life and health can lead to decisions that fail to adequately consider evidence of real benefits.MethodsThis descriptive study analyzed discrepancies between key arguments in judicial rulings that favored access to oncological drugs and the outcomes of related clinical trials. We reviewed 5 rulings issued in Ecuador between 2012 and 2018 that represented claims from 36 patients. The analysis focused on comparing judicial decision arguments against evidence from pivotal clinical trials regarding quality of life and overall survival.ResultsThe 16 litigated drugs were approved through accelerated pathways, of which 37.5% were classified by the European Medicines Agency (EMA) as requiring additional monitoring. While 97% of rulings stated that the litigated drugs improved quality of life or survival, clinical trials reported favorable benefits in less than 20% of cases for the judicially contested indications.ConclusionThese findings reveal significant discrepancies between available scientific evidence and the arguments supporting judicial decisions in cases involving access to oncological drugs in Ecuador.